2019
DOI: 10.1016/j.mito.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-reoxygenation of primary astrocytes results in a redistribution of mitochondrial size and mitophagy

Abstract: Astrocytes serve to maintain proper neuronal function and support neuronal viability, but remain largely understudied in research of cerebral ischemia. Astrocytic mitochondria are core participants in the metabolic activity of astrocytes. The objective of this study is to assess astrocyte mitochondrial competence during hypoxia and post-hypoxia reoxygenation and to determine cellular adaptive and pathological changes in the mitochondrial network. We hypothesize that during metabolic distress in astrocytes; mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 73 publications
(69 reference statements)
4
27
0
1
Order By: Relevance
“…It refers to selective sequestration of mitochondria by autophagosomes and subsequently delivers them to lysosomes for destruction and material recycle [10]. Previous studies have shown that mitophagy is mainly evident in neurons [36] and astrocytes [37] of the ischemic brain. However, it is controversial whether I/R-triggered mitophagy is beneficial or detrimental to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It refers to selective sequestration of mitochondria by autophagosomes and subsequently delivers them to lysosomes for destruction and material recycle [10]. Previous studies have shown that mitophagy is mainly evident in neurons [36] and astrocytes [37] of the ischemic brain. However, it is controversial whether I/R-triggered mitophagy is beneficial or detrimental to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of cerebral ischemic injury, the activation of glial cells can play a certain neuroprotective effect, but the excessive activation of glial cells can produce a series of inflammatory factors or mediators to mediate neuronal degeneration (90). Previous study has found that hypoxia and reoxygenation of astrocytes caused increased mitochondrial fission and mitophagy (91). In the rat cortex after cerebral ischemia and reperfusion, the activation of mitophagy in astrocytes is also found (83).…”
Section: Glial Mitophagy In Ischemic Strokementioning
confidence: 99%
“…During brain injury, astrocytes may release damaged mitochondria to minimize the amount of detrimental ROS and dysregulated Ca 2+ balance (66). Conversely, healthy mitochondria may also be donated from astrocytes to damaged neighboring neurons, increasing its viability (67). Moreover, Davis et al (68), firstly demonstrated that the exchange of mitochondria among neurons and astrocytes seem to work in a bidirectional way (68).…”
Section: Astrocyte-to-neurons Mitochondria Exchangementioning
confidence: 99%